2011
DOI: 10.1121/1.3652882
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional clear speech perception benefit for native and high-proficiency non-native talkers and listeners: Intelligibility and accentedness

Abstract: This study investigated how native language background interacts with speaking style adaptations in determining levels of speech intelligibility. The aim was to explore whether native and high proficiency non-native listeners benefit similarly from native and non-native clear speech adjustments. The sentence-in-noise perception results revealed that fluent non-native listeners gained a large clear speech benefit from native clear speech modifications. Furthermore, proficient non-native talkers in this study im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 54 publications
8
46
1
Order By: Relevance
“…This learning is assumed to be mostly implicit and at least to some degree context-specific (e.g., including adaptations specific to certain types of audiences, such as clear speech in the presence of noise, Smiljanic & Bradlow, 2005, and foreign directed speech, Scarborough, Brenier, Zhao, Hall-lew, & Dmitrieva, 2007;Smiljanic & Bradlow, 2011). In this view, language users can use perception of their own utterances and feedback from their interlocutors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This learning is assumed to be mostly implicit and at least to some degree context-specific (e.g., including adaptations specific to certain types of audiences, such as clear speech in the presence of noise, Smiljanic & Bradlow, 2005, and foreign directed speech, Scarborough, Brenier, Zhao, Hall-lew, & Dmitrieva, 2007;Smiljanic & Bradlow, 2011). In this view, language users can use perception of their own utterances and feedback from their interlocutors.…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, though, we assume that there are typically different ways of realizing the same or a near meaning-equivalent message -an assumption shared with most psycholinguistic work -and that these options differ in the extent to which they support the intended inference (in the current context). For example, a word can be articulated with more or less acoustic detail and this will affect its recognition (Smiljanic & Bradlow, 2011;Connine, 2004;Pitt, 2009). 1 Similarly, some syntactic forms will increase the probability of successful communication, compared to other structural choices.…”
Section: Introductionmentioning
confidence: 99%
“…Bradlow and Bent (2002) found that while native listeners displayed a clear speech benefit over conversational speech of 16 rationalized arcsine units (RAUs), a non-native group benefited by significantly less, around 5 RAUs, suggesting that at least some clear speech enhancements are language-specific and their exploitation depends on linguistic knowledge. More recently, Smiljanic and Bradlow (2011) reported that highly proficient nonnative listeners found clear speech enhancements as beneficial as native listeners, which they consider to further support the idea that clear speech strategies are to some extent language-specific and thus require a good command of the linguistic code in order to exploit them effectively.…”
Section: Introductionmentioning
confidence: 87%
“…The presentation order was randomized. Using a computer keyboard, participants rated how accented each sentence was on a 1-to-9 Likert scale: 1 ¼ no foreign accent; 9 ¼ very strong foreign accent (Smiljanic and Bradlow, 2011).…”
Section: Methodsmentioning
confidence: 99%